Responsibilities of Rowing Athletes in Achieving Learning Achievement - Hasmarita, Sony; Juditya, Silvy; Nur, Yasyfi Rayhan (STKIP Paasundan Press, 2023)
The purpose of this study was to determine the level of responsibility of rowing athletes in achieving learning achievements. This study uses a quantitative survey method. The population in this study were 28 athletes rowing TBR Cimahi City. The sampling technique in this study was to use total sampling technique. The sample in this study were all 28 athletes rowing TBR Cimahi City. The instrument used is a responsibility questionnaire. The results of research on the Responsibility of Rowing Athletes in Achieving Learning Achievements. There was 1 respondent in the very good category, as many as 9 respondents in the good category, there were 9 respondents in the moderate category, then there were 7 respondents in the unfavorable category, and there were 2 respondents in the very unfavorable category. that the average percentage of responsibility of TBR rowing athletes Cimahi City is 82%. So the conclusion of this study is that the level of Responsibility of Rowing Athletes in Achieving Learning Achievement is included in the very high category.